Hydrostatin-SN1, a Sea Snake-Derived Bioactive Peptide, Reduces Inflammation in a Mouse Model of Acute Lung Injury - Wu, Guosheng; Wang, Junjie; Luo, Pengfei; Li, An; Tian, Song; Jiang, Hailong; Zheng, Yongjun; Zhu, Feng; Lu, Yiming; Xia, Zhaofan (Frontiers in Pharmacology, 2017)
Snake venom has been used for centuries as a traditional Chinese medicine. Hydrostatin-SN1 (H-SN1), a bioactive peptide extracted from the Hydrophis cyanocinctus venom gland T7 phage display library, was reported to have the ability to reduce inflammation in a dextran sulfate sodium-induced murine colitis model. In this study, we sought to investigate the inhibitory potential of H-SN1 on inflammation in a murine model of lipopolysaccharide (LPS)-induced acute lung injury (ALI), and elucidate the anti-inflammatory mechanism in LPS-stimulated RAW 264.7 cells. In vivo, C57BL/6 male mice were intratracheally instilled with LPS or physiological saline with concurrent intraperitoneal injection of H-SN1 or saline alone. Lung histopathologic changes, lung wet-to-dry weight ratio, and myeloperoxidase activity in lung tissues were assessed. Total cell number, the protein concentration, and cytokine levels were determined in the bronchial alveolar lavage (BAL) fluid. In vitro, RAW 264.7 cells were treated with various concentrations of H-SN1 for 2 h followed by incubation with or without 1 μg/ml LPS for 0.5 or 24 h. The mRNA expression of inflammatory cytokines was determined via RT-PCR and protein levels in the supernatants were measured via ELISA. Extracellular-signal related kinase 1/2 (ERK1/2) and nuclear factor-κB (NF-κB) pathways were analyzed via western blot. H-SN1 improved pulmonary edema status, decreased vascular permeability, suppressed pro-inflammatory cytokine production, and lessened lung morphological injury. H-SN1 also dose-dependently inhibited the mRNA expression and release of TNF-α, IL-6, and IL-1β in LPS-stimulated RAW 264.7 cells. Moreover, H-SN1 inhibited the LPS-induced phosphorylation of ERK1/2 and the nuclear translocation of NF-κB. Our results suggest that H-SN1 could attenuate LPS-induced ALI in mice, which is associated with the anti-inflammatory effect of H-SN1. The mechanism might involve inhibiting the production of inflammatory cytokines by, at least in part, interfering with the ERK1/2 and NF-κB signaling pathways.